Occupational lead poisoning - Ramírez, Augusto V (2005)
Lead, a ubiquitous heavy metal, has been found in places as unlikely as Greenland’s fossil ice. Egyptians and Hebrews used it. In Spain, Phoenicians c. 2000 BC worked ores of lead. At the end of the XX century, occupational lead’s poisoning became a public health problem in developed countries. In non-developed countries occupational lead poisoning is still frequent. Diagnosis is directed to recognize lead existence at the labor environment and good clinical and occupational documentation. Differential diagnosis considers neurological and abdominal pain syndromes. Both blood lead and zinc-protoporphyrin levels are trustworthy and crucial analysis. In exposed workers, blood-lead can attain 40 ug/100 mL and even 80 ug/100 mL in unhealthy industries workers and zincprotoporphyrin is above 4 ug/g of hemoglobin. Treatment consists mainly in calcium disodium edetate, d-penicillamid lead’s quelantes, or the new di-mercapto succinic acid and 2-3 di-mercapto-1-propane sulfonic acid that have improved the therapeutic options, are less toxic and easier to manage. We highlight lead’s problem as a high-priority problem in public and occupational health, as well as a serious ecological problem.